2018
DOI: 10.1101/495432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An RNA-binding region regulates CTCF clustering and chromatin looping

Abstract: Mammalian genomes are folded into Topologically Associating Domains (TADs), consisting of celltype specific chromatin loops anchored by CTCF and cohesin. Since CTCF and cohesin are expressed ubiquitously, how cell-type specific CTCF-mediated loops are formed poses a paradox. Here we show RNase-sensitive CTCF self-association in vitro and that an RNA-binding region (RBR) mediates CTCF clustering in vivo. Intriguingly, deleting the RBR abolishes or impairs almost half of all chromatin loops in mouse embryonic st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 80 publications
6
25
0
Order By: Relevance
“…Finally, it is tempting to speculate a connection between our identified clusters of closely located CTCF binding sites on the genome and the reportedly observed 3D "clusters" (or "hubs") of CTCF protein molecules (Hansen et al, 2018b(Hansen et al, , 2018c. In particular, Hansen et al have proposed a guided mechanism where an RNA strand can bind to and gather together multiple CTCF protein molecules near cognate binding sites.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Finally, it is tempting to speculate a connection between our identified clusters of closely located CTCF binding sites on the genome and the reportedly observed 3D "clusters" (or "hubs") of CTCF protein molecules (Hansen et al, 2018b(Hansen et al, , 2018c. In particular, Hansen et al have proposed a guided mechanism where an RNA strand can bind to and gather together multiple CTCF protein molecules near cognate binding sites.…”
mentioning
confidence: 68%
“…In particular, Hansen et al have proposed a guided mechanism where an RNA strand can bind to and gather together multiple CTCF protein molecules near cognate binding sites. These CTCF molecule hubs apparently enhance the search 15 for target binding sites, increase the binding rate of CTCF to its related sites (also as part of the LMC model) and are often implicated in chromatin loop formation (Hansen et al, 2018b(Hansen et al, , 2018c. It is possible that our identified CTCF site clusters act synergistically with this mechanism as nearby sites for the concentrated CTCF molecules to bind.…”
mentioning
confidence: 86%
“…4D-E and fig. S8C)(31). In contrast, Pol II and active histone modifications mark robust short-range boundaries but are associated with weaker long-range insulators compared to CTCF/cohesin (Fig.…”
mentioning
confidence: 95%
“…Recently, we found that the maternal expression of Meg3, and possibly the lncRNA itself, prevents activation of Dlk1 as well (25). We hypothesise that the two mechanisms are linked, with either the Dlk1-Meg3 sub-TAD focusing or constraining the repressive function of the Meg3 expression or transcript, or conversely, with maternal Meg3 expression facilitating CTCF recruitment or its stability of binding at the DMR, possibly through direct RNA-CTCF contacts (32,33).…”
Section: Discussionmentioning
confidence: 90%